2017
DOI: 10.1007/978-1-4939-7046-9_19
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MicroRNAs in Thyroid Carcinoma

Abstract: MicroRNA (miRNA) are negative regulators of gene expression and subsequent protein production. This method of action translates into regulatory control over cellular processes, including development, signaling, metabolism, and apoptosis. A broad range of miRNA are shown to have abnormal expressions in thyroid cancers which could explain the pathology of tumor oncogenesis and disease progression. A review is conducted of the current research on miRNA dysregulation in thyroid cancers, including papillary thyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…In the past few years, several studies have focused on the expression profiles and biological roles of miRNA in PTC 17,33,34. An increasing number of miRNAs have been found to be dysregulated in PTC, and their dysregulation is believed to have important impacts on the formation and progression of PTC via a negative regulation of their target genes implicated in cellular biological behaviors 19,35,36. Hence, further investigation of the detailed roles of specific miRNAs in PTC might facilitate the identification of more effective targets for the treatment of patients with PTC.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, several studies have focused on the expression profiles and biological roles of miRNA in PTC 17,33,34. An increasing number of miRNAs have been found to be dysregulated in PTC, and their dysregulation is believed to have important impacts on the formation and progression of PTC via a negative regulation of their target genes implicated in cellular biological behaviors 19,35,36. Hence, further investigation of the detailed roles of specific miRNAs in PTC might facilitate the identification of more effective targets for the treatment of patients with PTC.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many miRNA signatures have been well characterized for PTC (17); however, but further investigation on the roles of dysregulated miRs in PTC development and progression is necessary for seeking more effective therapeutic strategies. In the present study, it was observed that miR-409-3p was frequently downregulated in PTC samples specimens and cell lines, consistent with its reduced expression in lung (18) and bladder cancer (19).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that miRNAs are aberrantly expressed in almost all types of human cancer, including PTC (12), colorectal cancer (13), lung cancer (14), glioblastoma (15) MicroRNA-766 inhibits papillary thyroid cancer progression by directly targeting insulin receptor substrate 2 and regulating the PI3K/Akt pathway and bladder cancer (16). Increasing evidence has revealed that various miRNAs are differentially expressed in PTC, and their dysregulation has been implicated in the regulation of PTC occurrence and development (17)(18)(19). Furthermore, miRNAs may have tumor suppressive or oncogenic roles in the progression of PTC and are able to regulate various cancer-associated biological processes, including cell proliferation, cell cycle progression, apoptosis, invasion, metastasis and epithelial-mesenchymal transition (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%